G protein-coupled receptor 35 attenuates nonalcoholic steatohepatitis by reprogramming cholesterol homeostasis in hepatocytes - Xiaoli Wei; Fan Yin; Miaomiao Wu; Qianqian Xie; Xueqin Zhao; Cheng Zhu; Ruiqian Xie; Chongqing Chen; Menghua Liu; Xueying Wang; Ruixue Ren; Guijie Kang; et al. (Elsevier, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. Fat accumulation "sensitizes" the liver to insult and leads to nonalcoholic steatohepatitis (NASH). G protein-coupled receptor 35 (GPR35) is involved in metabolic stresses, but its role in NAFLD is unknown. We report that hepatocyte GPR35 mitigates NASH by regulating hepatic cholesterol homeostasis. Specifically, we found that GPR35 overexpression in hepatocytes protected against high-fat/cholesterol/fructose (HFCF) diet-induced steatohepatitis, whereas loss of GPR35 had the opposite effect. Administration of the GPR35 agonist kynurenic acid (Kyna) suppressed HFCF diet-induced steatohepatitis in mice. Kyna/GPR35 induced expression of StAR-related lipid transfer protein 4 (STARD4) through the ERK1/2 signaling pathway, ultimately resulting in hepatic cholesterol esterification and bile acid synthesis (BAS). The overexpression of STARD4 increased the expression of the BAS rate-limiting enzymes cytochrome P450 family 7 subfamily A member 1 (CYP7A1) and CYP8B1, promoting the conversion of cholesterol to bile acid. The protective effect induced by GPR35 overexpression in hepatocytes disappeared in hepatocyte STARD4-knockdown mice. STARD4 overexpression in hepatocytes reversed the aggravation of HFCF diet-induced steatohepatitis caused by the loss of GPR35 expression in hepatocytes in mice. Our findings indicate that the GPR35-STARD4 axis is a promising therapeutic target for NAFLD.